Pendekatan Kepemimpinan Dalam Promosi Pendidikan Islam: (Analisis di Dayah Jamiah Al-Aziziyah Kabupaten Bireuen) - Hanafiah, Muktar (Yayasan Madinah Al-Aziziyah, 2023)
Educational marketing is crucial for institutions to compete in attracting students. Maintaining quality that meets societal demands is a challenge. Weak marketing can lead to a shortage of students, even for high-quality institutions, emphasizing the need for effective marketing strategies. Institutions must innovate in developing educational products that meet public needs and desires. This study examines the marketing strategies adopted by the leadership of Dayah Jamiah Al-Aziziyah in Samalanga District, Bireuen Regency, and factors influencing the success of Islamic education marketing there. Using a descriptive qualitative approach, the subjects of this research include the leadership, a teacher, and three female students of Dayah Jamiah Al-Aziziyah. Findings reveal that the marketing strategy at Dayah Jamiah Al-Aziziyah includes market segmentation, undifferentiated marketing, and mass marketing through social media and websites. The dayah also focuses on economic aspects by offering affordable fees and good educational quality. Success factors include moral education, discipline, administrative payment relief policies, and attention to students' health. The effective marketing strategy implemented by the dayah is expected to contribute to the development of Islamic education in Indonesia.